Efficacy and safety of topical 0.1% cannabidiol for managing recurrent aphthous ulcers: a randomized controlled trial - Chalapinyo Umpreecha; Kanokporn Bhalang; Dusadee Charnvanich; Jittima Luckanagul (BMC, 2023)
Abstract Background Although topical steroids constitute the first-line therapy for recurrent aphthous ulcers (RAUs), their long-term use often leads to candidiasis. Although cannabidiol (CBD) can be an alternative for pharmacologically managing RAUs due to its analgesic and anti-inflammatory in vivo effects, there is a lack of clinical and safety trials concerning its use. The aim of this study was to evaluate the clinical safety and efficacy of topical 0.1% CBD for managing RAU. Methods A CBD patch test was performed on 100 healthy subjects. CBD was applied on the normal oral mucosa of 50 healthy subjects 3 times/day for 7 days. Oral examination, vital signs, and blood tests were performed pre- and post-CBD use. Another 69 RAU subjects randomly received one of three topical interventions: 0.1% CBD, 0.1% triamcinolone acetonide (TA), or placebo. These were applied on the ulcers 3 times/day for 7 days. The ulcer and erythematous size were measured on day 0, 2, 5, and 7. Pain ratings were recorded daily. The subjects rated their satisfaction with the intervention and completed a quality-of-life questionnaire (OHIP-14). Results None of the subjects exhibited allergic reactions or side effects. Their vital signs and blood parameters were stable before and after the 7-day CBD intervention. CBD and TA significantly reduced ulcer size more than placebo at all time points. The erythematous size reduction was higher in the CBD intervention than the placebo on day 2, while TA reduced the erythematous size at all time points. The pain score in the CBD group was lower compared with placebo on day 5, whereas TA reduced pain more than placebo on day 4, 5, and 7. The subjects receiving CBD reported higher satisfaction than placebo. However, the OHIP-14 scores were comparable among the interventions. Conclusions Topical 0.1% CBD reduced ulcer size and accelerated ulcer healing without side effects. CBD exerted anti-inflammatory effects in the early stage and an analgesic effect in the late RAU stage. Thus, topical 0.1% CBD might be more appropriate for RAU patients who decline to take topical steroids, except for cases where CBD is contraindicated. Trial registration Thai Clinical Trials Registry (TCTR) Number TCTR20220802004. Retrospectively registered on 02/08/2022.